1995
DOI: 10.1074/jbc.270.5.2183
|View full text |Cite
|
Sign up to set email alerts
|

The DnaK Chaperone System of Escherichia coli: Quaternary Structures and Interactions of the DnaK and GrpE Components

Abstract: The DnaK (Hsp70), DnaJ, and GrpE heat shock proteins of Escherichia coli constitute a cellular chaperone system for protein folding. Substrate interactions are controlled by the ATPase activity of DnaK which itself is regulated by the nucleotide exchange factor GrpE. To understand the structure-function relationship of this chaperone system, the quaternary structures of DnaK, GrpE, and DnaK-GrpE complexes were analyzed by gel filtration chromatography, dynamic light scattering, analytical ultracentrifugation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
228
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(245 citation statements)
references
References 20 publications
15
228
1
1
Order By: Relevance
“…This molecular mass is about twice the molecular mass of the human GrpE monomer. This result is in good agreement with the analytical ultracentrifugation data generated for E. coli GrpE (16). The analysis of the crystal structure of E. coli GrpE confirms that this protein is a dimer with an elongated shape.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This molecular mass is about twice the molecular mass of the human GrpE monomer. This result is in good agreement with the analytical ultracentrifugation data generated for E. coli GrpE (16). The analysis of the crystal structure of E. coli GrpE confirms that this protein is a dimer with an elongated shape.…”
Section: Discussionsupporting
confidence: 79%
“…The elongated shape of GrpE is the most likely reason for the apparently much too high molecular mass calculated from molecular exclusion chromatography experiments (16). Several works have indicated that the elongated shape of GrpE serves the purpose of allowing its N terminus to also interact with DnaK-SBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it seems inappropriate at this time to form rigid models of the priming step based on stoichiometry data that require the action of specifically a monomer or a dimer of hsp70 on the receptor. It is possible that only one molecule of hsp70 is bound directly to and interacting productively with the receptor, and that under these conditions of assembly with purified proteins the receptor-bound hsp70 can associate with other molecules of hsp70 to form dimers and trimers, much as purified hsp70 and its homologs have been shown to do in solution (32)(33)(34). It is perhaps important to note that analysis of both the native and assembled hsp90⅐Hop⅐hsp70 machinery has revealed a molar ratio of 1 hsp70 per hsp90 dimer (6,18).…”
Section: Fig 4 Release Of Primed Gr⅐hsp70 Complex and Visualizationmentioning
confidence: 99%
“…Bacterial DnaK and its mammalian mitochondrial and cytoplasmic homologs self-associate in solution into dimers, trimers, and probably higher oligomers, with the equilibrium between these forms being dependent upon the concentration of the chaperone and the equilibrium being shifted toward the monomer by ATP or binding of peptide substrate (32)(33)(34). Under concentrated conditions, our purified hsp70 is predominantly dimeric on native gel electrophoresis with some trimers being detectable, yet under dilute conditions in reticulocyte lysate, the free hsp70 behaves as a monomer on molecular sieve chromatography (6), as did our purified hsp70 (data not shown).…”
Section: Stoichiometry Of the Primed Gr⅐hsp70mentioning
confidence: 99%